2019
DOI: 10.1016/j.japwor.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Happiness before and after an election: An analysis based on a daily survey around Japan’s 2009 election

Abstract: This paper investigates whether the Japanese voters became happy and/or unhappy due to the results of the General Election in 2009. We conducted a daily web survey for seven days before and after the election, obtaining 1068 responses. Estimating a fixed effects model, we found that supporters of the Democratic Party of Japan (DPJ), the winner, became significantly happier, and supporters of the Liberal Democratic Party of Japan (LDP) and New Komeito, the losers, became significantly unhappier on the day follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
0
12
2
4
Order By: Relevance
“…However, the gap in the happiness level between OMOTENASHI workers and others disappeared after two weeks, suggesting that the negative impact was temporary. (Impact of various variables on the happiness level did not persist in the long term (Tsutsui & Ohtake [29]), Kinari et al [30]]).…”
Section: Resultsmentioning
confidence: 99%
“…However, the gap in the happiness level between OMOTENASHI workers and others disappeared after two weeks, suggesting that the negative impact was temporary. (Impact of various variables on the happiness level did not persist in the long term (Tsutsui & Ohtake [29]), Kinari et al [30]]).…”
Section: Resultsmentioning
confidence: 99%
“…Tudomásunk szerint ez az első olyan kutatás, ami nemzetközi összehasonlításban vizsgálja a pártos elköteleződés és az egyéni boldogságszint közötti kapcsolatot. Bár ismerünk néhány korábbi eredményt arra vonatkozóan, hogy a választást megnyerő pártok támogatói lényegesen boldogabbak a választást követő napokban, mint a vesztes pártok támogatói (Gilbert et al 1998;Wilson-Meyers-Gilbert 2003;Kinari et al 2015;Pierce-Rogers-Snyder 2016), illetve, hogy ez a különbség kisebb mértékben, de az egész választási ciklusra kiterje-dően fennállhat (Curini-Jou-Memoli 2012; Patkós-Vay-Farkas 2012; Tsutsui-Yamane-Ohtake 2017), a fenti kutatások többsége csupán egy-egy választás adatait vizsgálta, és némelyik mindössze pár tucatnyi kísérleti alany bevonásával készült. A hatás robusztusságának vizsgálata céljából a kutatásunk a European Social Survey (ESS) adatait használja fel, adatbázisunk 2002 és 2015 között 30 európai országból tartalmaz megfigyeléseket, így összesen több mint 200000 megkérdezett válaszait elemezzük.…”
Section: Boldogok a Kormánypártiakunclassified
“…Ebből a nézőpontból a választási győzelem még akkor is növeli az egyének boldogságát, ha nem kötődnek különösebben a kormánypárthoz, melyre a szavazatukat adták. Ez az elmélet azokkal a kutatási eredményekkel áll összhangban, amelyek kimutattak ugyan különbséget kormánypárti és ellenzéki szavazók boldogsága között, de amelyek szerint ez a hatás rövid idővel, maximum egy héttel a választásokat követően eltűnik (Gilbert et al 1998;Wilson-Meyers-Gilbert 2003; Álvarez-Díaz-González-Radcliff 2010; Kinari et al 2015;Pierce-Rogers-Snyder 2016). Mintánkban átlagosan két évvel a választások után készültek az interjúk, és kevesebb, mint az interjúk fél százaléka készült a választásokat követő egy hónapon belül.…”
Section: Elméleti Keretunclassified
“…Many research works analyzed the outcome of mega sporting events such as the Olympics and the soccer world cup in the labor market of the host countries (e.g., Miyoshi and Sasaki [15], Banumann et al [16], Hagan and Maennig [17], Hagan and Maennig [18], and Hotochkiss et al [19]). It is observed that the Olympics increase employment by 17 %.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the Olympics increase employment by 17 %. (Hotochkiss et al [19]): There are arguments that mega sporting events ultimately have only minimal economic impact (Miyoshi and Sasaki [15], Hagan and Maennig [17], Hagan and Maennig [18], Jasmand and Maennig [20], and Baade and Matheson [21]). However, when we focus on specific industries, the hospitality industry, such as restaurants and hotels, benefitted from the Olympics.…”
Section: Introductionmentioning
confidence: 99%